1979
DOI: 10.1111/j.1365-2141.1979.tb03696.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Peripheral Blood Lymphocytes and Bone Marrow Infiltration in Non‐Hodgkin's Lymphoma

Abstract: The blood lymphocytes of 21 normal blood specimens, 20 patients with various malignant disorders and 63 patients with non-Hodgkin's disease lymphoma, all with lymphocyte counts below 6 x 10(9)/l, were examined by sheep red cell rosetting, fluorescent antisera to surface immunoglobulin and for sensitivity to colchicine. The results were correlated with bone marrow infiltration and lymph node histological findings. The ratio of kappa to lambda light chains in the surface immunglobulin was used to determine if an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 19 publications
(9 reference statements)
0
18
0
Order By: Relevance
“…A recent study demonstrated a monoclone of circulating B lymphocytes in 25/50 patients with NHDL, using surface markers (Garrett et al, 1979). The presence of a monoclone was shown to be closely associated with marrow infiltration.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study demonstrated a monoclone of circulating B lymphocytes in 25/50 patients with NHDL, using surface markers (Garrett et al, 1979). The presence of a monoclone was shown to be closely associated with marrow infiltration.…”
Section: Discussionmentioning
confidence: 96%
“…Lymphocyte surface-marker studies were performed and assessed as described previously (Garrett et al, 1979).…”
mentioning
confidence: 99%
“…With (Garrett et al, 1979;Johnson et al, 1985: igler et al. 1980; Lindemalm et al, 1985;Sobol et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoma cells have been detected in peripheral blood by routine morphological examination of the blood smear (Come et al, 1980;Dick et al, 1974;Foucar et al, 1982;Garrett et al, 1979;McKenna et al, 1975). Their presence in B-cell lymphoma has also been implied with k and .…”
mentioning
confidence: 99%
“…cells expressing either kappa or lambda light chains (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Blood cells that appear normal morphologically have in many cases been disclosed as monoclonal Bcells.…”
mentioning
confidence: 99%